2017
DOI: 10.3390/en10081097
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the Structure of Distribution Smart Grids with Renewable Generation against Abnormal Conditions: A Complex Networks Approach with Evolutionary Algorithms

Abstract: Abstract:In this work, we describe an approach that allows for optimizing the structure of a smart grid (SG) with renewable energy (RE) generation against abnormal conditions (imbalances between generation and consumption, overloads or failures arising from the inherent SG complexity) by combining the complex network (CN) and evolutionary algorithm (EA) concepts. We propose a novel objective function (to be minimized) that combines cost elements, related to the number of electric cables, and several metrics th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 133 publications
0
29
0
Order By: Relevance
“…The second category consists of energy sources that are renewed on a frequent basis (for, instance daily) such as wind turbines, solar photovoltaic (PV) panels, and stationary battery banks. The present increase of small-scale urban PV in buildings [3] and urban wind generators [4] can help home electricity consumers also become producers using the smart grid (SG) concept [5][6][7] and the microgrids approach [8,9].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The second category consists of energy sources that are renewed on a frequent basis (for, instance daily) such as wind turbines, solar photovoltaic (PV) panels, and stationary battery banks. The present increase of small-scale urban PV in buildings [3] and urban wind generators [4] can help home electricity consumers also become producers using the smart grid (SG) concept [5][6][7] and the microgrids approach [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…A review of the key concepts of smart grids can be found in Cuadra et al, . Specifically, Cuadra et al [5] explore the optimization of distribution smart grids with distributed renewable generation using a novel approach based on complex network concepts [10] with evolutionary algorithms. The use of evolutionary algorithms and other computational intelligence techniques in energy can be found in Ardabili et al, Cuadra et al and Jiang et al [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Distributed Energy Resource (DER) generations and microgrids: they provide the option to self-supplies local area when their feeder is disrupted [4,[86][87][88].…”
mentioning
confidence: 99%